PERSPEKTIF ILMU FALAK TERHADAP DETERMINASI ARAH KIBLAT DI ATAS KAPAL LAUT: Determination Of The Qiblate Direction On The Sea Ship Astrology Perspective - rezki dayat; Irfan; Thahir Maloko (HISABUNA: Jurnal Ilmu Falak, 2022)
The development of the times is so rapid from time to time, the determination of the Qibla direction on a ship can be known by using a software-based method (Application). Determining the direction of Qibla is very important for the benefit of Muslims in carrying out fard and sunnah worship while traveling or traveling long distances by using a marine vehicle. The objectives to be achieved in this paper are 1) To know and understand the method of determining the Qibla direction on a ship; and 2) To find out the determination of the Qibla direction on a ship from the Astrological Perspective. The author uses a qualitative research type with a syar'i and sociological approach. The main data collection technique was obtained from the use of the Muslim Pro application in determining the Qibla direction onboard a ship. And not only that, the author also uses data collection techniques obtained through other people or from a documentation in the form of written materials to complete the data to be described and analyzed from literature readings that are related to the determination of the Qibla direction onboard the Astronautical Science perspective.